Solve for x and y :
x + y = 1 → y = 1 - x
x ² + y ² = -1
x ² + (1 - x)² = -1
x ² + (1 - 2x + x ²) = -1
2x ² - 2x + 1 = -1
2x ² - 2x + 2 = 0
x ² - x + 1 = 0
x ² - x + 1/4 = -3/4
(x - 1/2)² = -3/4
x - 1/2 = ±√(-3/4)
x - 1/2 = ±√3/2 i
x = 1/2 ± √3/2 i → x = exp(± iπ/3)
y = 1 - (1/2 ± √3/2 i ) → y = -1/2 ± √3/2 i → y = exp(± 2iπ/3)
Then
x ⁷ + y ¹³ = exp(± 7iπ/3) + exp(± 26iπ/3)
… = exp(± iπ/3) + exp(± 2iπ/3)
since 7π/3 is equivalent to π/3, and 26π/3 is equivalent to 2π/3 (both modulo 2π).
In either case, we get
x ⁷ + y ¹³ = x + y = 1
so the answer is (2) 1.